Ensuring Pharmaceutical Quality: The Role of Stability Studies and Regulatory Guidelines: A Review - Leghari, Qurratul Ain; Noshad,; Anwar , Neha Tehreem; Syed, Yumna; Shuja , Ali Asgher; Ali , Mehtab (Indus Journal of Bioscience Research, 2025)
Objective: To ensure the quality of pharmaceutical products, stability studies are mandated. These studies adhere to guidelines established by organizations such as the International Conference on Harmonization (ICH) (e.g., ICH Q1AR2) and the World Health Organization (WHO). They evaluate how well the products maintain their physical, chemical, microbiological, and other essential properties under defined conditions. Methodology: This section dives into the world of stability testing for drugs and pharmaceuticals. We'll explore the different types of assessments used to monitor a product's quality and purity over time. We'll also delve into the specific methods employed to test stability, and unpack the key elements of well-designed and controlled stability testing protocol. Results: Stability studies are crucial for ensuring medications remain safe and effective throughout their shelf life. These studies follow strict regulations and test products under various storage conditions, mimicking real-world scenarios. This rigorous testing provides valuable evidence on how the medications degrade over time, guaranteeing their quality for patients. Conclusion: This review examines the critical role of stability studies in safeguarding the reliability and effectiveness of medications. By following established regulatory guidelines, these studies explore various methods to assess how well a drug maintains its quality over time. Ultimately, stability testing empowers us to confidently set and potentially extend the shelf life of pharmaceutical products, ensuring patients receive medications with the potency they deserve.